(untitled) - Rao, M. V. S. (Singapore, 1998)
Ultrahigh energy cosmic rays carry information about their sources and the intervening medium apart from providing a beam of particles for studying certain features of high energy interactions inaccessible at man-made accelerators. They can be studied only be the extensive air showers (EASs) they generate while passing through the Earth's atmosphere, since their fluxes are too low for the experiments of limited capability flown in balloons and satellites.
Keywords: Cosmic ray showers,Tia vũ trụ